#connected : 2015 sectoral debate, Wednesday, May 6, 2015 - Hanna, Lisa (Jamaica. Ministry of Youth and Culture KingstonJM, 2015)
Outlines the focus and work of the Ministry of Youth and Culture, Jamaica.